1999
DOI: 10.1007/pl00007648
|View full text |Cite
|
Sign up to set email alerts
|

Regional Pleural Filtration and Absorption Measured by Fluorescent Tracers in Rabbits

Abstract: In prone anesthetized rabbits, we used Evans blue-dyed albumin (EBA) to study regional pleural filtration and FITC dextran to study regional pleural absorption. Evans blue was injected intravenously, and the animals were ventilated for 6 h at either of two levels of ventilation. Postmortem the right rib cage was frozen and thawed before study. EBA fluorescence emitted from the rib cage surface was measured along the cranial-caudal axis near the mid chest with fluorescence videomicroscopy. Fluorescent light int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
1
11
0
2
Order By: Relevance
“…Tracing marker administered into the peritoneal cavity was found to travel via the diaphragm to the sternal lymphatics located in the ventral inner-wall of the thoracic cavity. Subsequently, the same drainage pattern was observed in many animals [4,7,9]. This lymphatic drainage route may be clinically useful in predicting the course of intraperitoneal cancer dissemination.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…Tracing marker administered into the peritoneal cavity was found to travel via the diaphragm to the sternal lymphatics located in the ventral inner-wall of the thoracic cavity. Subsequently, the same drainage pattern was observed in many animals [4,7,9]. This lymphatic drainage route may be clinically useful in predicting the course of intraperitoneal cancer dissemination.…”
supporting
confidence: 63%
“…This may be due to the pressure of the liver on the right surface of the diaphragm. The uptake of lymph from the peritoneal side of the diaphragm's surface depends on the mesothelial cells of the diaphragm surface [1,2,5,8,9]. There may be more stomata located in the mesothelium on the surfaces with organ contact than on surfaces with no organ contact.…”
Section: Discussionmentioning
confidence: 99%
“…Of these factors, the lymphatic drainage system via lymphatic stomata likely plays an important role (30)(31)(32)(33)(34), which may contribute up to approximately 75-80% of the fluid absorption rate in the abdominal and pleural cavities (33,35).…”
Section: Serosal Membranes Lymphatic Stomata and Coelomic Fluid Draimentioning
confidence: 99%
“…1,2 Of these factors, the lymphatic drainage system via the lymphatic stomata is considered to play an important role, contributing up to approximately 75%-80% of the fluid absorption rate in the serosal cavity. [1][2][3][4][5][6] Lymphatic stomata are small openings that enable direct communication between the lymphatic lumen and the serosal cavity. 7 Since apertures in the diaphragmatic peritoneum were first described, 8 numerous investigators have confirmed the existence of lymphatic stomata not only in the peritoneum but also in the pleura of various types of mammals, such as rabbits, 9 rats, [9][10][11] sheep, 12,13 monkeys, 14,15 golden hamsters, 16 and mice.…”
Section: Introductionmentioning
confidence: 99%